2006
DOI: 10.1111/j.1365-2958.2006.05055.x
|View full text |Cite
|
Sign up to set email alerts
|

The UGA3‐GLT1 intergenic region constitutes a promoter whose bidirectional nature is determined by chromatin organization in Saccharomyces cerevisiae

Abstract: SummaryTranscription of an important number of divergent genes of Saccharomyces cerevisiae is controlled by intergenic regions, which constitute factual bidirectional promoters. However, few of such promoters have been characterized in detail. The analysis of the UGA3-GLT1 intergenic region has provided an interesting model to study the joint action of two global transcriptional activators that had been considered to act independently. Our results show that Gln3p and Gcn4p exert their effect upon cis -acting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Gcn4p was suggested to contribute to the transcription of Gln3p-targeted genes, DAL1 and DAL5, which are important for uptake and degradation of the nitrogen source allantoin and for UGA3, a focus of their study (50,73). Those findings further support the idea that the transcription of genes involved in nitrogen assimilation can be coordinately regulated by Gcn4p and Gln3p, as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Gcn4p was suggested to contribute to the transcription of Gln3p-targeted genes, DAL1 and DAL5, which are important for uptake and degradation of the nitrogen source allantoin and for UGA3, a focus of their study (50,73). Those findings further support the idea that the transcription of genes involved in nitrogen assimilation can be coordinately regulated by Gcn4p and Gln3p, as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 73%
“…1) (85, 136). Among them, GLN1 and GDH2 were previously established as being sensitive to NCR (84), but GDH1 and GLT1 were not, although observations consistent with this view have been reported (65,129). It thus seems that the complete set of enzymes forming the heart of nitrogen metabolism in yeast is subject to NCR.…”
Section: Discussionmentioning
confidence: 56%
“…While these observations indicate that the transcription of GCN4 is subject to NCR, two other studies have highlighted a positive contribution of Gcn4 in NCR (118,128), thus suggesting some cross-regulation between NCR and GAAC (see Discussion). Yet another transcription factor gene classified as an NCR target is UGA3, in keeping with a recent report (65). This factor is responsible for induction by GABA of the transcription of genes involved in GABA catabolism (2,121).…”
mentioning
confidence: 56%
“…The mode of interaction in divergent promoters can be quite diverse. Coexpression can be explained by bidirectional transcription attributable to various factors, including common cis -regulatory elements (in MAL6T-MAL6S ) (Bell et al 1995) or chromatin organization (in UGA3-GLT1 ) (Ishida et al 2006). In contrast, some studies reported no dependence on gene orientation (Bae et al 2008) and others reported anticorrelated gene expression between divergent genes (Lin et al 2007).…”
Section: Discussionmentioning
confidence: 99%